Penguatan Regulasi Berbasis Kearifan Lokal Untuk Mewujudkan Pariwisata Berkelanjutan - Ainuddin, Ainuddin; Isnani, Atin Meriati (Jurnal Ilmiah Pengabdian dan Inovasi, 2026)
This article examines the importance of strengthening tourism regulations based on local wisdom in achieving sustainable tourism amid the rapid growth of the tourism sector. The objective of this community service is to enhance the understanding of communities and stakeholders regarding the integration of local wisdom values into tourism regulatory frameworks. The study employs a participatory approach through socialization, education, Focus Group Discussions (FGDs), and direct assistance to communities and relevant stakeholders. The findings indicate an increased level of awareness and understanding of the strategic role of local wisdom in supporting tourism governance. Furthermore, the integration of local wisdom values into regulatory frameworks is shown to promote a more inclusive, equitable, and sustainable tourism system. In conclusion, local wisdom serves as a fundamental foundation for strengthening tourism regulations, ensuring a balance between economic growth, cultural preservation, and environmental sustainability.